Debating the urban dimension of territorial cohesion - Medeiros, E. (2022)
The Territorial Cohesion goal was only included in the EU Treaty by 2009, with a view to promote a more balanced and harmonious European territory. One year earlier (2008), the European Commission (EC) published the ‘Green Paper on Territorial Cohesion—Turning territorial diversity into strength’. Neither one, nor the other, clearly defines the meaning of the Territorial Cohesion concept. The later, however, proposes three main policy responses towards more balanced and harmonious development: (i) Concentration: overcoming differences in density; (ii) Connecting territories: overcoming distance; and (iii) Cooperation: overcoming division. Although not explicitly, this document identifies several ‘urban questions’ to be dealt when promoting territorial cohesive policies: avoiding diseconomies of very large agglomerations and urban sprawl processes, combating urban decay and social exclusion, avoiding excessive concentrations of growth, promoting access to integrated transport systems and creating metropolitan bodies. In this light, this chapter proposes to debate the importance of the urban dimension to achieve the goal of territorial cohesion at several territorial levels.